PEMODELAN VULNERABILITAS AIR TANAH DANGKAL DI PANTAI SELATAN KABUPATEN BANTUL - YOGYAKARTA - Mardi Wibowo (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Groundwater quality, espicially shallow groundwater is very vulnerable topollution from residence, urban, agriculture, and industrial activity. All ofthe activity, to result waste and pollutant potentially, that can degradegroundwater quality, like as in southern coast of Bantul Resisence-Yogyakarta. So, it’s need modeling of vulnerability of shallow groundwaterin unconfined aquifer. Based on natural condition of southern coast ofBantul Residence, parameters are used in development this model aredepth of groundwater level, surface geological condition, soil condition, andaquifer media.Based on this model, vulnerability of southern coast in Bantul Residence, is: abaut 27,86 km (47,52%) is classified in vulnerable class, 16,23 km (27,69%) is very vulnerable, 5,49 km (9,37% is, poor vulnerable and 9,04 km (15,42%) is not vulnerable. Generally, groundwater vulnerability is degrade toward land.